Technology acceptance model (TAM) in understanding EFL learners’ use of web 2.0 tools - Kızıl, Aysel Şahin (My University, 2016)
Considered among the key technologies of the current world, Web 2.0 has been widely reported to be used in language education contexts; though, as implied in most cases, its success depends on how language learners perceive Web 2.0 tools. This study aims to investigate the perceptions of English as a Foreign Language (EFL) learners towards Web 2.0 tools within the framework of Technology Acceptance Model (TAM) which is one of the most commonly applied theory for delving into user acceptance of information and communication technologies. Data consisting of surveys of 572 EFL learners attending a preparatory program at a Turkish university were analysed through descriptive statistics. Findings are discussed in connection with such variables as awareness, perceived usefulness, perceived ease of use, attitudes towards use, behavioural intention and actual system usage through correlational analysis. The study concludes that EFL learners are aware of existence of Web 2.0 tools, though limited in variety, and find them acceptable and useful in general; however, their level of Web 2.0 technological acceptance for language learning is relatively lower. Also, perceived usefulness and perceived ease of use along with learners’ attitudes and ability to use are among the key predictors in determining the behavioural intention to use Web 2.0 technology.
Bildiri - Yayımlanmış
Keywords: EFL learners; Technology acceptance model (TAM); Web 2.0